Implemetasi Kebijakan Dinas Kesehatan Dalam Penanganan Gizi Buruk Pada Balita Di Kabupaten Enrekang - Nugroho, Eko Eryanto; Mahsyar, Abd; Usman, Jaelan (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to determine the implementation of health service policies in the handling of malnutrition in infants in Enrekang Regency. The study  used  qualitative research. The number of informants in this study was 5 people. Data collection were l observation, interviews with a number of informants were the head of the health department, the Public Health sector, nutrition program managers and parents. The technique of checking the validity of the data used triangulation, the method triangulation. The data analysis technique used interactive analysis. The results of this study showed that the implementation of policies carried out by the health department in handling malnutrition in children under five years old in Enrekang Regency was already good, it was seen that the communication aspect was already run well  because  there was pre-socialization, the  resources were available so  it was more easier, the disposition of the handling was carried out in the form of giving vitamins, and the bureaucratic structure of children and young women who worked together with the health center and the hospital, were also supporting and inhibiting factors as movers thinkers or planners to achieve an organizational goal and lack of vitamins and supplements.